2021
DOI: 10.1177/10499091211026675
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Quality Improvement Intervention to Improve Pediatric Palliative Care Consultation Processes

Abstract: Background: A critical aspect of pediatric palliative care consultations is the assessment and documentation of patient and family needs. While these assessments usually include a focus on physical pain, there is less standardization of assessments of other physical symptoms and psychosocial, emotional, or spiritual needs. Aims: To improve the breadth of assessment of psychosocial and emotional needs, screen for symptoms other than pain among pediatric patients utilizing palliative care services, and to increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…High-yield palliative care referral triggers do not necessitate translation into practice, and incorporating these triggers into a screening scale might improve referral [ 17 ]. This argument is supported by evidence that suggests screening scales [ 18 20 ], referral criteria [ 21 ], care algorithms [ 22 ], standardising practices [ 23 ] and periodic audits [ 24 ] have the potential to enhance integrated paediatric palliative care. Three studies from the United States showed that embedding palliative care providers in paediatric oncology settings was feasible, acceptable, and improved child and family outcomes [ 25 – 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…High-yield palliative care referral triggers do not necessitate translation into practice, and incorporating these triggers into a screening scale might improve referral [ 17 ]. This argument is supported by evidence that suggests screening scales [ 18 20 ], referral criteria [ 21 ], care algorithms [ 22 ], standardising practices [ 23 ] and periodic audits [ 24 ] have the potential to enhance integrated paediatric palliative care. Three studies from the United States showed that embedding palliative care providers in paediatric oncology settings was feasible, acceptable, and improved child and family outcomes [ 25 – 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] The literature on quality improvement and resource utilization of pediatric palliative care initiatives focuses on chronic illnesses, particularly the pediatric oncology population. [18][19][20] One single-center study of 167 patients aged 0-25 years with acute life-threatening illness or injury in the absence of complex chronic conditions showed that palliative care was involved in 20% of these patients' care and were able to provide earlier goals of care discussions and documentation of end-oflife preferences. 21 Our pilot study is the first quality improvement project specifically focused on a population of pediatric and adolescent trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…After screening the title and abstract of 6183 papers (excluding duplicates) for relevance to the subject, 131 papers were selected. A total of 67 articles [ 1 , 7 , 12 , 13 , 14 , 15 , 16 , 17 , 21 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , …”
Section: Methodsmentioning
confidence: 99%